Pengaruh Pemberian Asi Predominan Dan Tipe Pola Asuh Terhadap Tingkat Kecerdasan (IQ) Pada Anak Usia 3-6 Tahun Di Paud Kasih Ibunda Kecamatan Mojoroto Kota Kediri - Sumy Dwi Antono; Finta Isti Kundarti; Triatmi Andri Yanuarini (coba, 2014)
Intelligence is one of the capital to navigate the future. This intelligence is influenced by two fundamental factors, namely genetic and environmental factors. Genetic factors have contributed to 30-40 percent, the rest is environmental factors that play a role. The purpose of this study was to determine the effect of predominant breastfeeding and type of parenting style on the level of intelligence (IQ) of children aged 3-6 years in Kindergarten Earth Kasih Bunda Kediri. The study design used was an observational analytic populations are mothers of children aged 3-6 years in kindergarten Earth Kasih Bunda Kediri as many as 30 people. The sample in this study as much as 28taken by random sampling technique. multivariate data analysis with linear regression techniques to look at the influence of predominant breast feeding and type of parenting style on the level of intelligence (IQ) of children.The results of multivariate analysis showed that the variables simultaneously predominant breastfeeding and type of parenting style affects the level of intelligence (IQ) in which parenting variables have the greatest influence with the value of α = 0.016, followed by predominantly breast-feeding variable with a value of α = 0.043. Can be concluded that the longer the predominant breastfeeding, the better type of parenting can be predicted increase a child's IQ test results. Key words: Predominant breastfeeding, parenting, IQ